2021
DOI: 10.1187/cbe.20-12-0276
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Characterization of the Expert Problem-Solving Process in Science and Engineering: Guidance for Teaching and Assessment

Abstract: A study of the problem-solving process used by skilled practitioners across science, engineering, and medicine revealed that their process can be characterized by a set of 29 specific decisions. They select and use frameworks of disciplinary knowledge to make those decisions. This work will enable better assessment and teaching of problem-solving skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…Visually, arrows connecting the Action/Cue/Sensemaking bubbles point in all directions on the diagram, indicating that theorists frequently jump between different points in their overall process as they refine their goals and progress toward a satisfactory research product. The nonsequential nature of the theorists' processes aligns with previous results on the nature of authentic decision-making by STEM researchers [25]. Still, construction of these process diagrams allowed us to split theorists' research projects into several loosely defined phases, with the acknowledgement that the order of research activities is flexible.…”
Section: A Phases Of Theory Projectssupporting
confidence: 64%
See 2 more Smart Citations
“…Visually, arrows connecting the Action/Cue/Sensemaking bubbles point in all directions on the diagram, indicating that theorists frequently jump between different points in their overall process as they refine their goals and progress toward a satisfactory research product. The nonsequential nature of the theorists' processes aligns with previous results on the nature of authentic decision-making by STEM researchers [25]. Still, construction of these process diagrams allowed us to split theorists' research projects into several loosely defined phases, with the acknowledgement that the order of research activities is flexible.…”
Section: A Phases Of Theory Projectssupporting
confidence: 64%
“…We utilize similar methods to Price et al, who used a cognitive task analysis approach to conduct retrospective interviews with 52 STEM professionals about how they solved a particular problem in their research (see Section III for details on cognitive task analysis methods). The authors identified a set of 29 primary decision points that experts use across disciplines, such as deciding what problems are important in their field and which predictive framework to use [25].…”
Section: Background a Expert Problem Solvingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, group members can provide validating feedback to one another, which may also increase their confidence in solutions. Remarkably, it was recently shown that scientific experts consistently make twenty-nine specific types of decisions in the process of solving authentic problems, irrespective of their discipline (Price, Kim, Burkholder, Fritz, & Wieman, 2021). While this number of decisions is tractable, it is not few.…”
Section: Discussionmentioning
confidence: 99%
“…Developing these skills is especially important for undergraduate students aspiring to become STEM professionals, as those are the skills that they will utilize on a daily basis in their future careers [9]. However, little research has aimed to characterize how physicists solve real-world problems related to their research, and has typically focused on engineers [10], multiple STEM fields [11], or physics graduate students [12]. Few have focused exclusively on physics researchers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%